Draft Eighth Five Year Plan 1990-95 and Annual Plan 1991-92 Hill Area Sub-Plan Vol.-I Sectoral Review - Planning Commission (Planning Commission, 1990)
Demographic factors are very much influenced by the physical characteristics. Due to hard existence and inadequacy of basic facilities small settlements appear on landscape of the hilly tracts. However, in the flat areas along rivers and at the foot hills, large settlements are to be found. The choice of a village site here is conditioned by such factors as availability of fertile land, supply of water, proximity to economic activity centres etc. The villages are usually small. The average population of a village of the region in 1981 was 261. Most of the villages in the region (13388 or 89 percent) had population below 500.
Government of Uttar Pradesh Hill Development Department
Government of Uttar Pradesh Hill Development Department